A Comparative Analysis of the Effects of Objective and Self-Assessed Financial Literacy on Stock Investment Return - Liao, Kaicheng; Zhang, Yuchen; Lei, Hanyun; Peng, Geng; Kong, Wei (Frontiers in Psychology, 2022)
Until now, comprehensive and quantitatively meaningful analyses of stock market participation outcomes of retail investors have been limited by data sources in developing countries. This paper devises a special questionnaire related to stock investment to measure the financial literacy (FL) and stock investment return (SIR) for the subjects with stockownership in China, and theoretically and empirically study the effects of objective FL, self-assessed FL, and their composite FL on SIR. The results of comparative analysis show that self-assessed FL has a greater effect on SIR than objective FL, and the effect is mediated by risk preference. In addition, we find that the competent and overconfident respondents have higher SIR, while underconfident respondents cannot gain from stock market. Also we find the risk preference has a positive mediating effect in the relationship between competence and overconfidence and SIR, and a negative mediating effect in the relationship between underconfidence and SIR. We thus conclude that those confident investors can gain more stockholding return via taking more risks regardless of the level of their actual financial knowledge. Our findings would be a meaningful complement to the studies of stock market participation.